A home-based smart health model. (June 2020) - Bedón-Molina, John; Lopez, Mario J; Derpich, Ivan S
This article is about an architectural hardware-software model creation—home-based smart health model—to boost healthcare to a higher position within society. As an emerging field, smart health modeling is still insufficient. Current smart health services are hospital centered, data are scattered and application dependent, and health service provision presents attention delays. Analyses of Internet of things, Internet of medical things, and smart health applications potentials are the bases for the proposed home-based smart health model. The model aims to facilitate the smart health development and strengthening. To evaluate whether the model does what it must do, first, check lists on how the model complies with current and future devices and applications, smart health impacts and smart health potentialities, and second, a case study analyses the model conformity through an Internet of things sophisticated cloud app.